2016
DOI: 10.1590/s0102-86502016001300005
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Hyperbaric Oxygen Therapy promotes successful healing in patients with refractory Crohn's disease

Abstract: PURPOSE: To investigate de adjunctive effect of Hyperbaric Oxygen Therapy in a group of patients with refractory Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Positive outcomes with hyperbaric oxygen therapy for treating perineal Crohn's disease have been reported in small case series 11,16,17 . However, patient characteristics and outcome parameters were not well defined in these studies, leading to a significant risk of bias.…”
Section: Introductionmentioning
confidence: 99%
“…Positive outcomes with hyperbaric oxygen therapy for treating perineal Crohn's disease have been reported in small case series 11,16,17 . However, patient characteristics and outcome parameters were not well defined in these studies, leading to a significant risk of bias.…”
Section: Introductionmentioning
confidence: 99%
“…These five patients received an average of 31.2 HBOT sessions, and all five patients demonstrated a satisfactory response to HBOT therapy. None of the five patients experienced adverse side effects (21).…”
Section: Pyoderma Gangrenosummentioning
confidence: 88%
“…Of these eight patients, one demonstrated complete heal-ing of his/her ulcer, five had improvement but not complete healing of their ulcers, one had stabilization of his/her ulcer, and one had worsening of ulcers after discharge (20). A study published by Feitosa et al in 2016 investigated the effect of HBOT in patients with refractory Crohn's disease (21). The endpoint of the study was complete healing of pyoderma gangrenosum and perianal disease and complete closure of enterocutaneous fistulas.…”
Section: Pyoderma Gangrenosummentioning
confidence: 99%
“…The latter represents a difficult phenotype of the disease that can require intensive medical therapy, wound care, surgical intervention 3 and sometimes an adjunctive HBO. 4 HBO is an interesting therapeutic approach, although its mechanism of action is not totally clear. Previous studies demonstrated the effectiveness of HBO in a model of experimental colitis by decreasing tissue damage.…”
Section: Dear Editormentioning
confidence: 99%
“…These immune and non‐immune complications may present as open wounds such as metastatic CD and perianal fistulizing Crohn’s disease (pCD). The latter represents a difficult phenotype of the disease that can require intensive medical therapy, wound care, surgical intervention 3 and sometimes an adjunctive HBO 4 …”
mentioning
confidence: 99%